2020
DOI: 10.3390/ijms21020547
|View full text |Cite
|
Sign up to set email alerts
|

Open Data for Differential Network Analysis in Glioma

Abstract: The complexity of cancer diseases demands bioinformatic techniques and translational research based on big data and personalized medicine. Open data enables researchers to accelerate cancer studies, save resources and foster collaboration. Several tools and programming approaches are available for analyzing data, including annotation, clustering, comparison and extrapolation, merging, enrichment, functional association and statistics. We exploit openly available data via cancer gene expression analysis, we app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…Furthermore, we found decreased proliferation and cell cycle arrest of ZNF554-transfected cells, which might be due to the downregulation of several cyclin-dependent kinases (CDK2, CDK9, CDK10, CDK13, CDK17), and five (CCNC, CCND3, CCNE2, CCNG1, CCNG2) out of six cyclin genes. This is in strong concordance with recent studies, one showing the anti-glioma effect of CDK inhibitors already in preclinical/clinical use [45], the other finding several CDKs and cyclin genes amongst top hub nodes in glioma network analysis [46].…”
Section: Znf554 As a Potential Tumor Suppressor In Gliomassupporting
confidence: 91%
“…Furthermore, we found decreased proliferation and cell cycle arrest of ZNF554-transfected cells, which might be due to the downregulation of several cyclin-dependent kinases (CDK2, CDK9, CDK10, CDK13, CDK17), and five (CCNC, CCND3, CCNE2, CCNG1, CCNG2) out of six cyclin genes. This is in strong concordance with recent studies, one showing the anti-glioma effect of CDK inhibitors already in preclinical/clinical use [45], the other finding several CDKs and cyclin genes amongst top hub nodes in glioma network analysis [46].…”
Section: Znf554 As a Potential Tumor Suppressor In Gliomassupporting
confidence: 91%
“…Many such targets have been discovered with the application of high-throughput sequencing; however, inconsistencies exist between DEGs in different studies. 14 On the basis of previous work, we comprehensively analyzed hub genes associated with survival and prognosis in glioma, but which have rarely been studied or have been reported in other tumors but not in glioma, [15][16][17][18][19] using RRA and WGNA bioinformatics methods. A co-expression network previously constructed using WGCNA showed that some hub genes correlated with clinical traits of glioma samples in CGGA and TCGA datasets.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the existence of an open database is very important. The complexity of cancer disease requires a large amount of data as a supporting basis, and the existence of an open database can accelerate related research and save researchers’ resources ( 16 ). Therefore, this retrospective study included histopathological slides of H&E-stained tissue samples from two cohorts of glioblastoma patients.…”
Section: Methodsmentioning
confidence: 99%